2022
DOI: 10.21608/ejmr.2022.252258
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia in Primary School Children in Beni-Suef (Prevalence and Clinical Spectrum)

Abstract: The aim of current study was to detect prevalence and clinical presentation of iron deficiency anemia (IDA) in primary school children in Beni-Suef and to assess their risk factors. This crosssectional survey was conducted on randomly selected primary school children with microcytic hypochromic anemia of both genders aged from 6 years -12 years in Beni-suef governorate.The prevalence of IDA was 26.6% among children 6-12 years of age. Socioeconomic factors (such as mother education, residence, nutritional statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In children aged less than 5 years, IDA affects more than 40%. Among children 6-12 years of age, reported IDA prevalence was 12%, 26.6%, 29% in Qena governorate, Beni-suef and Elmenofya governorates, respectively (Mabrouk et al 2022;El-Asheer et al 2021). Other studies reported variable prevalence of anemia, with the 55.7% recorded among schoolchildren in Lower Egypt, 54.1% among preschool children and 52% among adolescents (Data and on Iron Deficiency Anemia in Egypt 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In children aged less than 5 years, IDA affects more than 40%. Among children 6-12 years of age, reported IDA prevalence was 12%, 26.6%, 29% in Qena governorate, Beni-suef and Elmenofya governorates, respectively (Mabrouk et al 2022;El-Asheer et al 2021). Other studies reported variable prevalence of anemia, with the 55.7% recorded among schoolchildren in Lower Egypt, 54.1% among preschool children and 52% among adolescents (Data and on Iron Deficiency Anemia in Egypt 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among children 6-12 years of age, reported IDA prevalence was 12%, 26.6%, 29% in Qena governorate, Beni-suef and Elmenofya governorates, respectively. 7,8 Other studies reported variable prevalence of anemia, with the 55.7% recorded among schoolchildren in Lower Egypt, 54.1% among preschool children and 52% among adolescents. 9 Screening of infants with one or more risk factors for ID would allow treatment of ID in the pre-anemic stage, thereby preventing its associated mental, motor, and behavior effects.…”
mentioning
confidence: 98%